Plant Growth Responses of Apple and Pear Trees to Doses of Glyphosate - CARVALHO,L.B. (2016)
ABSTRACT Glyphosate is commonly used for intra-row weed management in perennial plantations, where unintended crop exposure to this herbicide can cause growth reduction. The objective of this research was to analyze the initial plant growth behavior of young apple and pear plants exposed to glyphosate. Glyphosate was sprayed on 2-year-old 'Gala' apple and 'Abbè Fetel' pear plants at doses from 18 to 720 g per hectare of acid equivalent (a.e.). The plant height of neither species was not significantly reduced (less than 1%) by any glyphosate dose at 240 days after spraying, whereas the stem diameter and the dry mass of stem and leaves were reduced by 720 g a.e. ha-1. The glyphosate dose required to reduce the aboveground dry mass by 50% was 162 and 148 g a.e. ha-1 for apple and pear, respectively. Aboveground dry mass was reduced 2% and 6% for apple and pear plants, respectively, at 720 g a.e. ha-1. Hormesis was not observed in either species at doses down to 18 g a.e. ha-1. Both species showed low susceptibility to glyphosate; however apple was less susceptible than pear.